Laccase production by Lepista sordida - Cavallazzi,José Renato Pereira (2004)
A Lepista sordida laccase has been characterized. Laccase and manganese peroxidase were detected in liquid medium with ammonium phosphate, yeast extract and ammonium molybdidate as nitrogen sources after 3 days of cultivation. Laccase optimal temperature and pH were 45ºC and 3.5, respectively.